Marie Heurtin - Améris, Jean-Pierre (S.l. : Liberty Productions, 2014)
"Marie Heurtin is born both blind and deaf. Sister Marguerette wins her trust and teaches her how to express herself"--IMDb, September 10, 2015.
In French.
Isabelle Carré, Ariana Rivoire, Brigitte Catillon.
Sources used: video container; Copyright catalog online; IMDb, September 10, 2015.
Keywords: Biographical films; Feature films; Fiction films